Substituição da farinha de peixe pelo farelo de soja em dietas para juvenis de curimba - Fabregat, Thiago El Hadi Perez; Pereira, Thiago Scremin [UNESP]; Boscolo, Camila Nomura [UNESP]; Alvarado, Julian David [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP] (Inst Pesca, 2011)
Replacement of fishmeal by soybean meal in juvenile curimba (Prochilodus lineatus) diets was evaluated. Five isonitrogenous (26% crude protein) and isocaloric (4,000 kcal of gross energy kg(-1)) diets with 0, 25, 50, 75 and 100% of replacement were used. Fish (3.71 +/- 0.54 g) were distributed in 25 tanks (120 liters). The diets were provided for 84 days. Total replacement of fishmeal (100%) by soybean meal worsened weight gain, feed conversion and protein efficiency ratio. An increase in carcass fat was observed at the expense of reducing protein percentage, as well as an increase in hepatosomatic index. It was concluded that replacing 75.0% fish meal by soybean meal (33.2% of inclusion) did not affect the animal growth, although there been observed changes in corporal composition and hepatic hyperplasia.
Replacement of fish meal by soybean meal in diets for juveniles of curimba
Keywords: Protein source; Prochilodus lineatus; animal protein; vegetal protein; fish nutrition